Innovation and Circular Economy in Tourism - Vargas-Sánchez, Alfonso (2021)
The transition towards a Circular Economy, that is, towards an economy oriented towards waste elimination, is one of the major vectors for innovation and change in this century, to which the tourism sector is also part. In this context, the aim of this paper is twofold: on the one hand, to expose the principles of application of the Circular Economy to that industry, with particular reference to the new circular business models; and, on the other hand, to present the first advances in this field at the level of a tourist destination in the province of Huelva (Spain). The exploratory study carried out reveals the priorities of tourism companies, in line with certain contributions that exist in the literature. The awareness among business people seems to exist, but collective action is lacking at the destination level to channel it into concrete actions articulated in a plan.